2011
DOI: 10.1371/journal.pbio.1000608
|View full text |Cite
|
Sign up to set email alerts
|

The “Parahippocampal Place Area” Responds Preferentially to High Spatial Frequencies in Humans and Monkeys

Abstract: A visual brain area that is thought to encode higher-level "place" information responds instead to lower-level "edge" information. A corresponding brain area is demonstrated in non-human species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
126
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(156 citation statements)
references
References 47 publications
24
126
5
1
Order By: Relevance
“…Thus, the reduction of higher frequency component is likely to have little effect on the difference in the responses observed in this study. Furthermore, an additional analysis confirmed that the specularity-induced activations were not restricted in the regions representing central visual field which are more sensitive to high spatial frequencies than those representing more peripheral visual field (Henriksson et al, 2008;Rajimehr et al, 2011;Sasaki et al, 2001); the effect of the scrambling on the responses was even consistently larger in the peripheral regions than in the central regions (Supplementary analysis 2 and Supplementary Fig. 2).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, the reduction of higher frequency component is likely to have little effect on the difference in the responses observed in this study. Furthermore, an additional analysis confirmed that the specularity-induced activations were not restricted in the regions representing central visual field which are more sensitive to high spatial frequencies than those representing more peripheral visual field (Henriksson et al, 2008;Rajimehr et al, 2011;Sasaki et al, 2001); the effect of the scrambling on the responses was even consistently larger in the peripheral regions than in the central regions (Supplementary analysis 2 and Supplementary Fig. 2).…”
Section: Discussionmentioning
confidence: 61%
“…However, this is not likely the case considering the spatial frequency tunings of BOLD responses in the visual cortex. Several fMRI studies have shown that early visual areas are most sensitive to relatively low spatial frequency (typically peaked at about 1-2 cycles/°) and are less sensitive to high spatial frequency (7 cycles/°or higher) (Henriksson et al, 2008;Rajimehr et al, 2011;Sasaki et al, 2001;Singh et al, 2000). Moreover, the amplitudes of higher frequency were relatively smaller in our stimuli.…”
Section: Discussionmentioning
confidence: 64%
“…34), which are thought to be homologous to scene-selective sites in humans, namely, (i) the transverse occipital area (TOS) and (ii) the parahippocampal place area (PPA) (35), respectively. In human subjects, rectilinear objects and shapes also preferentially activate these scene-selective areas (36)(37)(38). However, as scene-selective areas were not localized in our monkeys, this idea could not be directly tested.…”
Section: Significancementioning
confidence: 82%
“…It has already been established that the fusiform and parahippocampal gyri are involved in face, object and scene recognition (Epstein, Harris, Stanley, & Kanwisher, 1999;Epstein & Kanwisher, 1998;Grill-Spector, 2003;Haxby et al, 2001;Tanaka, 1996). These regions were also recently shown to be sensitive to low-level properties of stimuli such as spatial frequencies (Goffaux et al, 2010;Kauffmann, Ramanoël, Guyader, Chauvin, & Peyrin, 2015;Musel et al, 2014;Rajimehr, Devaney, Bilenko, Young, & Tootell, 2011). These activations are therefore consistent with Bar and colleagues' model of visual perception (Bar, 2003(Bar, , 2007Bar et al, 2006) which postulate that visual analysis begins with the parallel extraction of different elementary attributes at different spatial frequencies, and that, at neurobiological level, LSF content of an image is rapidly projected through magnocellular pathways from the occipital cortex to the orbitofrontal cortex, where it activates plausible interpretations of the visual input.…”
Section: Connectionmentioning
confidence: 99%